Post-prandial carbohydrate ingestion during 1-h of moderate-intensity, intermittent cycling does not improve mood, perceived exertion, or subsequent power output in recreationally-active exercisers - O'Neal Eric K; Poulos Sylvia P; Wingo Jonathan E; Richardson Mark T; Bishop Phillip A (Taylor & Francis Group, 2013)
Abstract Background This study compared the effects of ingesting water (W), a flavored carbohydrate-electrolyte (CE) or a flavored non-caloric electrolyte (NCE) beverage on mood, ratings of perceived exertion (RPE), and sprint power during cycling in recreational exercisers. Methods Men (n = 23) and women (n = 13) consumed a 24-h standardized diet and reported 2-4 h post-prandial for all test sessions. After a familiarization session, participants completed 50 min of stationary cycling in a warm environment (wet bulb globe temperature = 25.0°C) at ~ 60-65% of heart rate reserve (146 ± 4 bpm) interspersed with 5 rest periods of 2 min each. During exercise, participants consumed W, CE, or NCE, served in a counterbalanced cross-over design. Beverage volume was served in 3 aliquots equaling each individual's sweat losses (mean 847 ± 368 mL) during the familiarization session. Profiles of Mood States questionnaires (POMS) were administered and blood glucose levels were determined pre- and post- sub-maximal cycling. Following sub-maximal exercise, participants completed 3 30-s Wingate anaerobic tests (WAnT) with 2.5 min rest between tests to assess performance. Results Blood glucose was higher (p < 0.05) after 50 min of submaximal cycling just prior to the WAnT for CE (6.1 ± 1.7 mmol/L) compared to W (4.9 ± 1.5 mmol/L) and NCE (4.6 ± 1.2 mmol/L). Nonetheless, there were no differences among treatments in peak (642 ± 153, 635 ± 143, 650 ± 141 watts for W, NCE, and CE, respectively; p = 0.44) or mean (455 ± 100, 458 ± 95, 454 ± 95 watts for W, NCE, and CE, respectively; p = 0.62) power for the first WAnT or mean (414 ± 92, 425 ± 85, 423 ± 82 watts, respectively; p = 0.13) power output averaged across all 3 WAnT. Likewise, RPE during submaximal exercise, session RPE, and fatigue and vigor assessed by POMS did not differ among beverage treatments (p > 0.05). Conclusions Carbohydrate ingestion consumed by recreational exercisers during a 1-h, moderate-intensity aerobic workout did not alter mood or perceived exertion, nor did it affect subsequent anaerobic performance under the conditions of this study. Drinking caloric sport beverages does not benefit recreational exercisers in a non-fasted state.